Clinical impact of "minimal" right ventricular pacing on atrial arrhythmias: results from the prospective multi-center worldwide EMERALD study. (3rd October 2022) - Di Cori, A; Taggeselle, J; Giaccardi, M; Degand, B; Bernhardt, J; Fazi, A; Gonzalez Chana, B; Olivier, A; Clark, R; Bongiorni, M G
Abstract: Background/Introduction: Unnecessary right ventricular pacing (RVP), typically the result of pacing forced by the atrio-ventricular delay (AVD), can have deleterious effects such as atrial arrhythmias (AA) and heart failure (HF). Previous studies have shown that these increased risks occur when unnecessary RVP exceeds 40%, leading to the development of pacing modes to reduce the amount of unnecessary RVP and minimize these risks. Purpose: The EMERALD (AssEssment of CoMorbiditiEs & Atrial ArRhythmiA Burden In DuaL-Chamber PaceD Patients) Study was a real-world registry designed to assess the impact of RVP burden on the risk of developing AA. The primary endpoint was the difference in incidence of persistent/permanent AA in subjects with high (>40%) and low (<40%) RVP. Methods: EMERALD was a non-interventional, prospective, observational, multi-center registry conducted at 186 centers in 12 countries. The study enrolled subjects without a previous history of persistent or permanent AA implanted with a dual-chamber (DR) pacemaker according to ESC or ACC/AHA/HRS guidelines. Devices could be implanted as de-novo therapy, generator replacement or an upgrade in therapy. All implanted devices were approved for commercial use by local regulatory authorities. Programming was left to the investigators' discretion. Subjects were followed for at least 24 months. Persistent/permanent AA was defined as: a) >22 hours/day of AA for >7 consecutive days; b) permanent/persistent AA diagnosed during any follow-up visit; c) an AA-related ablation carried-out; d) a cardioversion performed during any follow-up visit. Results: Eligible follow-up data were available for n=3477 subjects with a RVP value. The population was nearly evenly split between High RVP (47.7%) and Low RVP (52.3%). In the High RVP group, 11.7% fulfilled at least one criterion for persistent/permanent AA versus 9.1% in the Low RVP group (p=0.006). The primary endpoint was met. A reanalysis of the data was performed first looking at quartiles of %RVP. Based on this, the threshold of RVP was changed from 40% to 1% (High RVP>1%; Low RVP<1%). Using this new RVP threshold, 13.1% of patients in the High RVP group fulfilled at least 1 criterion for persistent/permanent AA versus 3.4% in the Low RVP group (p<0.0001). Conclusions: The EMERALD Study confirmed the results of previous studies showing that limiting unnecessary RVP to <40% is beneficial in reducing the risk of AA in unselected DR pacemaker patients. Moreover, it showed for the first time that even small amounts of unnecessary RVP (>1%) significantly increases the risk of AAs, underlining the need to target very low RVP with efficient modes to reduce RVP. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): MicroPort CRM (Clamart, France)